Assessment of Radiological Hazards in Soil, Water and Plants Around Coal Power Plant - S. Murniasih; D. S. Prabasiwi; S Sukirno (PPIKSN-BATAN, 2022)
The existence of a Coal-Fired Power Plant (CFPP) is suspected to affect the environment quality, especially the increment of natural radionuclides content which is found in coal as raw material.Therefore, systematic analysis of natural radionuclides (210Pb, 234Th, 238U, 228RA, 40K, 226RA and232Th) in water, soil, and plantwere conducted to establish a database of environmental contamination in the area around a CFPP. This research was conducted in the area around Adipala Cilacap CFPP which operates with two towers. Samples were taken from three locations around the Adipala CFPP based on the secondary wind direction data from Indonesian Agency for Meteorological, Climatological, and Geophysics in the 2018 dry season. Samples were prepared in the Radiochemistry Laboratory, Center for Accelerator Science and Technology, BATAN.The concentration of radioactivity in environmental samples were analyzed using gamma spectrometry with a high purity germanium detector for 24hours after reaching its secular equilibrium. The result of samples analysesshown that the mean value of the radionuclides specific activities (210Pb, 234Th, 238U, 228RA, 40K, 226RA and232Th) for water, cassava leaves, grass, and soil were 0.789 Bq/L, 14.685 Bg/kg, 15.036 Bq/Kg, and 75.083 Bq/kg, respectively. The mean of radium equivalent activity (Raeq)for water, cassava leaves, grass, and soil were 1.692, 30.792, 18.699 and 137.513 Bq/kg, respectively. The absorbed dose rate (ADR)for water, cassava leaves, grass, and soil were0.775, 14.332, 8.627, and 64.135 nGy/h, respectively, whilst the annual effective dose rate (AEDR) were 0.004, 0.070, 0.042, and 0.315 mSv/y. The mean of external and internal hazard indices(Hex and Hin) for water, cassava leaves, grass, and soil were 0.005 and 0.006, 0.083 and 0.129, 0.050 and 0.078, and 0.371 and 0.554, respectively, while the mean of excess lifetime cancer risk (ELCR)wre 0.014×10-6, 0.246×10-6, 0.148×10-6, and 1.101×10-6. According to the calculation of radiation hazard index in this research, it was understood that all parameters of all samples were within acceptable limits by the world average value reported by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR).